KAJIAN KELAYAKAN PEMBANGUNAN JALAN ELAK SISI UTARA KOTA LANGSA BERDASARKAN ANALISA EKONOMI TRANSPORTASI - Ramli Ramli; Sofyan M. Saleh; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
The construction of medium and infrastructure of transportation has to be followed by the population growth. The trend to divide a regency / city into new separate one was perceived from the theorem of public welfare. This perception generates a big problem throughout Indonesia. Central Bureau of Statistics (2015) stated that the most populous city after Banda Aceh and Lhokseumawe is Langsa. Population of the city increased after the expansion in Langsa in term of motor vehicle. The congestion emerges at the peak hours, between 7.30 to 8.30 AM, 12.30 to 1.30 PM and 3.30 to 4.30 PM IWST. To anticipate this problem, the government of Langsa city in 2015 constructed a new road in the northern area, when the eastern area is not as effective since the width of the road is varied and it needs substantial cost for the construction. On the other hand, the existing road (national road) aquire longer travel time to access the office, education and shopping centre. Therefore, author was interested to observe these 3 (three) road, which generate a result stating that the time required to travel in the existing road is 1.15 hours and 0.03 hours in the alternative road for each one-way travel. The aimof this research is to analyze the benefit for road users by applying consumer surplus method and the public perception in terms of economy based on the Vehicle Operating Cost (VOC), saving of travel time and economic feasibility study based on Benefit Cost Ratio (BCR), Net Persen Value (NPV), Economy Internal Rate Return (EIRR) and sensitivity analysis.